Figurative Language in Damilare Kuku’s the Anointed Wife - Adetunji, Bukunmi (Optimality, 2025)
Literary texts are major instruments for the analysis of styles evident in the use of language.The majority of previous studies on literary texts thathave explored figurative language focus on poetic forms of literature with little attention to the prosaic form. Thus, this study investigatedthe deployment of figurative language in Damilare Kuku’s The Anointed Wife, one of the short stories in the author’s collection titled Nearly all Men in Lagos are Mad. This analysis was based on the theoretical framework of linguistic pragmatics that affords the ability to uncover linguistic depths via consideration of contexts. The study adopted a purposive sampling technique to identify the various instances of figurative speeches which were important to the construction of meaning in the selected extracts and employed a descriptive-analytical method. The study revealed how society places certain expectations on people who are separated as religious icons and how these people strive to live up to the expectations of society. It demonstrated the holy family's deceitful attempts to hide their transgressions to maintain their social standing. The linguistic pragmatic approach proved apt in unveiling the linguistic pattern of figurative expressions used to portray the church family, the society and the scandal. More studies could be done using another linguistic technique to analyse the same story or examine figurative expressions in any other story in Kuku’s collection.